OP33 Developing A Public Version Of A Health Technology Assessment Report. (2017) - Fearns, Naomi; Riches, Emma; Kelly, Joanna; Macpherson, Karen
Abstract : INTRODUCTION: As the Health Technology Assessment (HTA) community moves towards greater levels of Patient and Public Involvement (PPI), the need to communicate with the public about the results and impact of HTA, and of PPI itself, is also increasing. DECIDE was a European Commission funded collaborative project arising from the GRADE working group, which developed and evaluated strategies for effectively communicating the recommendations from clinical guidelines to a multiple stakeholders. The Scottish Intercollegiate Guidelines Network (SIGN) led the work stream on patients and the public (1, 2). We extended the findings to develop a patient/public version of an HTA on Antimicrobial Wound Dressings (AWDs). The clinical and cost effectiveness evidence was inconclusive (3) which increased the importance of engagement with clinical and patient/public stakeholders. METHODS: A literature review, and a series of focus groups and user testing informed the development of a set of principles for designing patient versions of guidelines (1, 2). Using these principles developed by the DECIDE collaboration, a patient version of the HTA was developed, in partnership with public volunteers and a standing public communications advisory group. RESULTS: We incorporated key facilitators of usability, such as distinct branding as material for the public, a clearly communicated purpose, and the layering of information. Other facilitators included a "friendly" and accessible tone which was achieved by the use of colour, icons, simple language and charts, and brief chunked text. While feedback about clarity, design and usefulness was generally positive, some public reviewers were concerned by the level of uncertainty and complexity in the findings. CONCLUSIONS: Using the principles from the DECIDE project, it is feasible and useful to develop public versions of an HTA report. The patient version is currently informing the development of educational material for patients/public about chronic wounds and AWDs by the Scottish Government. However, it remains a challenge to balance the complexity and uncertainty underlying evidence-based recommendations, with the need to provide accessible, understandable, and yet accurate information about them for the public.